2019
DOI: 10.1016/j.bpj.2019.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Two-Color Spatial Cumulant Analysis Detects Heteromeric Interactions between Membrane Proteins

Abstract: Fluorescence fluctuation spectroscopy can be used to measure the aggregation of fluorescently labeled molecules and is typically performed using time series data. Spatial intensity distribution analysis and fluorescence moment image analysis are established tools for measuring molecular brightnesses from single-color images collected with laser scanning microscopes. We have extended these tools for analysis of two-color images to resolve heteromeric interactions between molecules labeled with spectrally distin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Next, we tested whether the same approach can be used for FPs with overlapping emission in the red region of the visible spectrum, which generally suffer from reduced SNR in FFS applications ( Dunsing et al, 2018 ; Foust et al, 2019 ). Therefore, we performed SFSCS measurements on HEK 293T cells co-expressing mp-mCherry2 and mp-mApple.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we tested whether the same approach can be used for FPs with overlapping emission in the red region of the visible spectrum, which generally suffer from reduced SNR in FFS applications ( Dunsing et al, 2018 ; Foust et al, 2019 ). Therefore, we performed SFSCS measurements on HEK 293T cells co-expressing mp-mCherry2 and mp-mApple.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, spectral approaches require accurate detection of photons in each spectral bin. A previous study using the same detection system reported intrinsic cross-talk between adjacent spectral bins ( Foust et al, 2019 ). However, since the methodology presented here is based on temporal (SFSCS) or spatial (RSICS) correlation (both excluding the correlation at zero time or spatial lag), this issue can be neglected in our analysis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…GNG2 (G protein subunit gamma 2) expression is positively correlated with adipocyte size [ 46 ], and its upregulation can directly activate PI3K I B , thereby activating the PI3K-Akt pathway [ 47 ]. This pathway is also regulated by the Gβγ subunits of the trimer G protein complex formed by GNB1 and GNG2 [ 48 49 ]. Gβ1γ2 produces phosphoinositol by stimulating phospholipase Cβ, activating MAPK and Akt [ 50 ].…”
Section: Discussionmentioning
confidence: 99%